Impact of event experience towards satisfaction among e-sport event’ participants - Nur Ain Shafiqah Dzulkefli; Nur Aisyah Huwaida Mohd Nor; Nur Aisyah Huwaina Mohd Nor; Nur Amilya Nasuha Amran (2023)
This study aims to examine the effect of event experience on satisfaction among e-sports participants. The independent variables of this study consist of consumer-to-consumer interactions, effective communication and online content engagement. Next, this study has 3 objectives to examine the relationship between online consumers to consumer interaction and satisfaction among e-sport participants, to examine the relationship between effective communication and satisfaction among e-sport participants and to determine the relationship between online content engagement and satisfaction among e-sport participants. This study is believed to be able to give a significant picture to the audience consisting of the general public. Next, this research will choose a probability or random sampling technique. In addition, questionnaire surveys will be used for data collection. The questionnaire distributes through interview and collects data among the respondents who handle and involve in e-sport participant. The survey was conducted by face to face. Keywords: E-sport, viewers, satisfaction and experience.